Istihsan sebagai Sumber dan Metode Hukum Islam - Kadenun Kadenun (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2018)
Istihsan is the legal settlement of a mujtahid against a problem that deviates from the provisions of the law applied to similar problems, because there is astronger reason for doing such a deviation or a fair deed to a legal problem by looking at other laws, because the existence of something stronger with theexistence of justice. Istihsan is defined as the source and method of Islamic law, since it is established on the basis of research into cases and laws that itappears that the use of qiyas is the application of the general proposition (kulli) to the particular proposition (juz‟i) which is sometimes in some the cases leadto the loss of human merit, because these cases have their own specificities as well as istihsan set based on research on syara texts‟ which shows that Allahthe Wise move from some cases that can be used qiyas or generally nash to the law others who give generosity and reject conscience, such as Allah forbidcarrion, blood, pork, and what is slaughtered in the name of Allah. Therefore, the scholars (who accept istihsan) agree that the source of law used as legalpropositions and make it as the basis of Istihsan‟s law is the Qur‟an and asSunnah. While the various istihsan namely the transfer of the law from qiyaszhahir to qiyaskhafi, the transfer of laws defined by the common nash to a special nash, and the shift law kulli law juz‟i. The refutation of Imam Syafi‟i against istihsan, among others, Prophet Muhammad SAW never gives instructions by using istihsan as well as send a friend gives instructions with it, istihsan is not have clear limits / standard criteria to distinguish between haq and bathil, and istihsan is not referring to nash, but it refers to reason alone.